Treatment of military-related post-traumatic stress disorder: challenges, innovations, and the way forward. (2nd January 2019) - Forbes, David; Pedlar, David; Adler, Amy B.; Bennett, Clare; Bryant, Richard; Busuttil, Walter; Cooper, John; Creamer, Mark C.; Fear, Nicola T.; Greenberg, Neil; Heber, Alexandra; Hinton, Mark; et al.
Abstract: Post-traumatic stress disorder (PTSD) is one of the common mental disorders in military and veteran populations. Considerable research and clinical opinion has been focused on understanding the relationship between PTSD and military service and the implications for prevention, treatment, and management. This paper examines factors associated with the development of PTSD in this population, considers issues relating to engagement in treatment, and discusses the empirical support for best practice evidence-based treatment. The paper goes on to explore the challenges in those areas, with particular reference to treatment engagement and barriers to care, as well as treatment non-response. The final section addresses innovative solutions to these challenges through improvements in agreed terminology and definitions, strategies to increase engagement, early identification approaches, understanding predictors of treatment outcome, and innovations in treatment. Treatment innovations include enhancing existing treatments, emerging non-trauma-focused interventions, novel pharmacotherapy, personalized medicine approaches, advancing functional outcomes, family intervention and support, and attention to physical health.